On mythical Dewaruci, Manunggaling kawula-Gusti and other non-trivial Javanese logic - Victor Christianto; Florentin Smarandache; Sori Tjandrah Simbolon (The New Perspective in Theology and Religious Studies, 2022)
Discourses on logic have been for a long time predominated by Aristotelian logic, especially that is the case in the West. Although since early 20th century there are new development towards many-valued logic, for instance by Lukasiewicz etc, and also fuzzy logic theory by Lotfi Zadeh; and also in recent years there is development by one of us (FS) on Neutrosophic Logic, Plithogenic Logic etc. But still the general public usually are only accustomed to Aristotelian way. More recently, there are growing interests to consider African, Asian and also Native American logic. Nonetheless there is very rare discussion on Javanese logic, except perhaps a report by P. Stange. This article will consider some variations of logic which may show non-triviality of Javanese logic. Hopefully more readers are interested to consider this theme further.